Andrea Dworkin – najbardziej znienawidzona feministka - Klejdysz, Natalia (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2007)
On April 9, 2005, Andrea Dworkin, one of the most controversial figures of the second wave of feminism, died in Washington. Her statements against violence and pornography had rather weak theoretical foundations. Her few attempts to provide a broader background or to give reasons for the discrimination against women are failures: they are superficial and chaotic. Yet Dworkin was not a theoretician of the feminist movement, but a practitioner, or even its creator. Her preoccupation with the struggle against pornography resulted from her own traumatic experience. Dworkin liked to provoke. She was not attractive, which she ostentatiously emphasized. She shocked with her language. However, besides excessive vulgarisms, her statements reveal the profound passion with which she defended her views. Referring to the emotions of her readers and listeners, she did not conceal her own emotions, therefore her texts ooze with honesty and naturalness. Loathed by anti-feminists, rejected by the majority of feminists, she contributed to the creation of the radical dimension of modern feminism.